2022
DOI: 10.1111/jam.15764
|View full text |Cite
|
Sign up to set email alerts
|

Identification of antibacterial metabolites produced by a marine bacterium Halobacillus marinus HMALI004

Abstract: Aims: This study examined and characterized the extract for metabolites of Halobacillus marinus HMALI004 to understand their antibacterial activities against opportunistic marine pathogens, that is, Vibrio parahaemolyticus and Vibrio cholerae. Methods and Results:The bacterial strain HMALI004 was characterized as H. marinus, and an antibacterial spectral test revealed its inhibition against two opportunistic marine pathogens (V. parahaemolyticus and V. cholera). Fermentation broth of strain HMALI004 was subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…B. hwajinpoensis was frst isolated from sea water from Hwajinpo Beach, East Sea in Korea [30], and its heterotrophic nitrifcation-aerobic denitrifcation efects on water purifcation by removing inorganic nitrogen and total nitrogen were subsequently reported [31]. Halobacillus as a major ecosystem-adapted microbial component could survive from extreme environments due to its stronger survivability and fexible adaptability, such as salt lakes, hypersaline sediments and soils [32][33][34]. Some reporters have reported its outstanding capacity of inhibiting fungi activity thereby promoting the growth of plants [34,35], while some reporters have reported that Halobacillus from a shrimp pond exhibited antibacterial potencies against the opportunistic marine pathogens of Vibrio parahaemolyticus and Vibrio cholerae by producing antimicrobial compounds [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. hwajinpoensis was frst isolated from sea water from Hwajinpo Beach, East Sea in Korea [30], and its heterotrophic nitrifcation-aerobic denitrifcation efects on water purifcation by removing inorganic nitrogen and total nitrogen were subsequently reported [31]. Halobacillus as a major ecosystem-adapted microbial component could survive from extreme environments due to its stronger survivability and fexible adaptability, such as salt lakes, hypersaline sediments and soils [32][33][34]. Some reporters have reported its outstanding capacity of inhibiting fungi activity thereby promoting the growth of plants [34,35], while some reporters have reported that Halobacillus from a shrimp pond exhibited antibacterial potencies against the opportunistic marine pathogens of Vibrio parahaemolyticus and Vibrio cholerae by producing antimicrobial compounds [32].…”
Section: Discussionmentioning
confidence: 99%
“…Halobacillus as a major ecosystem-adapted microbial component could survive from extreme environments due to its stronger survivability and fexible adaptability, such as salt lakes, hypersaline sediments and soils [32][33][34]. Some reporters have reported its outstanding capacity of inhibiting fungi activity thereby promoting the growth of plants [34,35], while some reporters have reported that Halobacillus from a shrimp pond exhibited antibacterial potencies against the opportunistic marine pathogens of Vibrio parahaemolyticus and Vibrio cholerae by producing antimicrobial compounds [32]. Meanwhile, although some unique Bacillaceae genera was presented in the earthen ponds, such as Talassobacillus, Paenibacillus, Fictibacillus, Ornithinibacillus, Oceanobacillus, Solibacillus, Lysinibacillus, Virgibacillus, and Brevibacillus, the concentration of these bacteria was not high.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to assisting the hypersaline microflora in maintaining regular metabolic processes and osmotic balance maintenance, the compatible solutes also prevent microbial proteins from denaturation, increasing their capacity to withstand significant changes in the surrounding saline environment ( 7 ). Since hypersaline microflora are well adapted to extreme salt conditions, they have garnered significant interest in various biotechnological applications ( 8 11 ). Their diverse metabolic capabilities and resilience to extreme environments have made them valuable candidates.…”
Section: Introductionmentioning
confidence: 99%